2016
DOI: 10.4025/actasciagron.v38i1.25638
|View full text |Cite
|
Sign up to set email alerts
|

<b>Nutritional status, yield and composition of peach fruit subjected to the application of organic compost

Abstract: ABSTRACT. The purpose of this study was to evaluate the nutritional state, yield and composition of peaches on peach trees subjected to the application of organic compost to the soil. This experiment was . Avaliou-se o teor de nutrientes totais nas folhas, componentes de produção, produção por planta e hectare e a composição dos frutos em 2008 e 2009, logo depois da colheita e 30 dias após armazenamento. A aplicação de composto orgânico no solo, aumenta os valores de componentes de produção e a produção de pês… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…The tendency for both compost and mulch to increase leaf K was also documented by Marsh et al (1996) in organic apple. Although Toselli et al (2012) and de Melo et al (2016) found no effect of compost on the nutrient content of peach leaves despite increased yields.…”
Section: Tree Leaf Nutrientsmentioning
confidence: 89%
“…The tendency for both compost and mulch to increase leaf K was also documented by Marsh et al (1996) in organic apple. Although Toselli et al (2012) and de Melo et al (2016) found no effect of compost on the nutrient content of peach leaves despite increased yields.…”
Section: Tree Leaf Nutrientsmentioning
confidence: 89%
“…Amino acids (arginine, asparagine, isoleucine, lysine, serine, threonine, valine, leucine, phenylalanine, tryptophan, tyrosine, proline, and alanine) also contribute to the flavour of fruit and are found in peaches in different concentrations depending on the cultivar [15,16]. Among the mineral elements, they contain nitrogen, phosphorus, potassium, calcium, magnesium, iron, manganese, zinc, cooper, chromium, nickel, cobalt, lead, selenium, and fluoride [17,18]. Similar to apricots, the glycoside amygdalin (26%), protein amandine (3.8%), enzymes, lactase, and oleic acids are present in peach kernels.…”
Section: Introductionmentioning
confidence: 99%
“…Epidermis and flesh firmness, fruit hue, chroma, TSS, TTA and total antioxidant activity were modelled as target variables. True negative specimens were outnumbered (10)(11)(12)(13)(14)(15)(16)(17) for carotenoids and phenolic compounds in order to derive foliar nutrient standards at high target levels. The number of true negative specimens (32-59) sufficed for most target variables to compute nutrient standards.…”
Section: Fruit Yield and Quality Impacted By Key Features In Machine Learning Modelsmentioning
confidence: 99%
“…Fertilization, mainly with nitrogen (N), has impact on the composition of foliar nutrients, as well as on peach yield and quality [12][13][14][15][16][17]. Nitrogen fertilization extends the fruit development period, and it explains these fruits' capacity to sink carbohydrates and nutrients [18].…”
Section: Introductionmentioning
confidence: 99%